Sinusoidal Pulse Width Modulation Berbasis Lookup Table untuk Inverter Satu Fase Menggunakan 16-Bit Digital Signal Controller - Yohan Fajar Sidik; Danang Wijaya; Eka Firmansyah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
Inverter as one equipment relates closely to the renewable energy sector gain more and more important role in utilizing renewable energy widely. The inverter converts dc to ac form by a specific switching strategy. In this research, the switching strategy employed unipolar sinusoidal pulse width modulation (SPWM). The switching schemes were obtained by synthesis from sine lookup table that the width of pulses were obtained from simulation of PSIM. The aim of this research is to create a switching scheme in a software and then implemented in16-bit digital signal controller (DSC). Experiment in lab scale has been done to verify the proposed unipolar SPWM. The results showed that SPWM signals were easier generated in 16-bit digital signal controller (DSC). Other that, feature of PWM in this DSC has been supporting in inserting dead-time to avoid shoot through current at IGBT.